The Adyar library bulletin : vol. 14 - Brahmavidya; Governmental Research Association (U.S.) (New York : Tax Foundation, 1950)
Beginning Nov. 1948 includes material received by the Tax Foundation and the Governmental Research Association.
SERBIB/SERLOC merged record
Keywords: Taxation -- United States -- Bibliography -- Periodicals; Finance, Public -- United States -- Bibliography -- Periodicals